Lipoid proteinosis with vesicular lesions in a 2-year old boy. - Agarwal, S.; Chander, R.; Singh, M. (European Journal of Pediatric Dermatology, 2017)
Lipoid proteinosis is a rare genetic disease characterized by infiltration of hyaline material into the skin, mucosae, larynx and internal organs. Vesiculobullous lesions may occur early in the course and are either missed or misdiagnosed as epidermolysis bullosa. We report a rare case of lipoid proteinosis in a 2-year-old boy who presented with yellowish plaques, pock-like scars, and on subsequent visit, with multiple tense vesicles. The characteristic histopathological features of the vesicles helped in clinching the diagnosis.